Role of Fundus Fluorescein Angiography in Preproliferative Diabetic Retinopathy - Alyscia Cheema, Sorath Noorani (Pakistan Journal of Ophthalmology, 2008)
Purpose: To identify subtle areas of ischemia and extent of capillary nonperfusion, not visible clinically and to differentiate intra-retinal microvascular abnormalities from neovascularization. Material and Methods: Fundus fluorescein angiography of 25 patients having PPDR unilaterally or bilaterally was performed in eye department of JPMC from October 2001 to December 2002. Fundus fluorescein angiography was used as an important diagnostic tool to show exact location and extent of vascular changes of PPDR. Diabetic patients who had PPDR in one or both eye, clear media, no history of allergic reactions and normal renal profile were selected for fundus fluorescein angiography. Argon panretinal photocoagulation was planned in patients who already had complications of diabetic retinopathy in other eye and in patients who were unable to attend follow up visits, which is a major problem in our society. Results: Out of 25 patients 9 patients (36%) showed areas of capillary dropout on angiogram, which were not visible on clinical examination. Intraretinal microvascular abnormalities were confirmed in 13 patients (52%) along with areas of capillary nonperfusion. Two patients (8%) were proved to have neovessels on angiogram. One patient (4%) showed no additional finding on angiogram but only confirmed the clinical findings. Argon laser panretinal photocoagulation was performed on 24 eyes of 15 patients (60%). One patient (4%) had green laser photocoagulation around IRMA only. Nine patients (36%) were advised strict diabetic control and follow up visits to monitor progression of disease and need of treatment Conclusion: Fundus fluorescein angiography was of the greatest assistance in showing the exact location of retinal vascular abnormalities and extent of capillary dropout, which were asymptomatic lesions, but a major threat to the sight of patient.